Analisis Kelayakan Investasi Menggunakan Metode Discounted Cash Flow pada Tambang Aspal PT. Wijaya Karya Bitumen di Desa Nambo Kecematan Lasalimu, Kabupaten Buton, Sulawesi Tenggara - Triyanchy Afaz; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Wijaya Karya Bitumen is a company that plans to mine asphalt with an IUP area of 100 HA in Nambo Village, Lasalimu District, Buton Regency, Province of Sulawesi Tenggara. The total reserves are 5.945.000 tons with a selling price of IDR 270.000 / ton which is estimated to have a mining life of 16 years. This study aims to analyze the feasibility of investing in asphalt mining in terms of technical, economic and environmental aspects, using the discounted cash flow (DCF) feasibility analysis method to see whether a mine with asphalt production is feasible or not. The investment feasibility analysis parameters used are net present value (NPV), internal rate of return (IRR), pay back period (PBP) and profitability index (PI).The results of this study, obtained cash out flow of IDR 646.677.059.124 and cash in flow of IDR 2.088.966.982.500. Based on the discounted cash flow (DCF) method, the NPV results were IDR 206.854.298.263, an IRR of 15.99%, PBP for 3 years and 3 months and a PI of 3,127.Keywords : Investment Feasibility, Discounted Cash Flow (DCF), Technical Aspects,Economic Aspects, and Environment.